National Unemployment Demonstration, 1933 (1933)
1933 1918-1939 "National Unemployment Demonstration, 1933" [T0310.jpg], 1933 The National Joint Council (TUC and Labour Party) and the Co-operative Union organised a massive demonstration in London on 5 February 1933. There was a march, led by members of the Blacksmiths' Union on horseback in full regalia, from the embankment to a rally attended by 300,000 people in Hyde Park. Demonstrations were held in 23 other cities in Britain on the same day.